Fiber-optic chemical sensing with Langmuir-Blodgett overlay waveguides - Flannery, D.; James, Stephen W.; Tatam, Ralph P.; Ashwell, Geoffrey J. (Osa Optical Society of America, 1999)
Fiber-optic chemical sensing has been demonstrated with a side-polished single- mode optical fiber, evanescently coupled to chemically sensitive Langmuir- Blodgett (LB) overlay waveguides. The sensors exhibit a channel-dropping response centered on a wavelength that is dependent on the thickness and the refractive index of the overlay waveguide. It has been shown that pH-sensitive organic dyes proved to be suitable materials fur the formation of an overlay waveguide whereas LB deposition provides the required thickness control. A theoretical model of the sensor response, based on the Kramers-Kronig relations and phase matching of the guided modes within the optical fiber and overlay waveguide, shows good agreement with experimental results.
Keywords: absorption line